Initial evaluation of fruit of accessions of Persea schiedeana Nees for nutritional value, quality and oil extraction. (15th April 2018) - López-Yerena, A.; Guerra-Ramírez, D.; Jácome-Rincón, J.; Espinosa-Solares, T.; Reyes-Trejo, B.; Famiani, F.; Cruz-Castillo, J.G.
Highlights: Fruits of several accessions of Persea schiedeana Nees were evaluated. A large variability in fruit size and oil/dry matter contents among accessions was observed. A significant relationship between fruit dry matter and oil contents in the fruits was found. The oils extracted from fruits had a good fatty acid composition and antioxidant capacity. A first picture about phenol contents and antioxidant capacities of fruits and seeds was provided. Abstract: Persea schiedeana Nees is an underutilized and very little known species whose fruit is consumed in Mesoamerica where it grows wild. This study was carried out to evaluate: 1) the variability of fruit characteristics of different accessions; 2) the effects of centrifugation and microwave treatment on extracting oil from the fruit and on its qualitative characteristics; 3) the nutraceutical characteristics of the fruit and seeds of different accessions. The results showed a large variability in fruit size and oil/dry matter contents among the different accessions. There was a significant relationship between the dry matter and oil contents in the pulp. The combined use of centrifugation and microwave treatments gave high oil extraction yields (67–68%). The oils had good fatty acid composition and antioxidant capacity. The results gave an initial picture about the total phenol contents and antioxidant capacities in the seeds and in the different parts of the fruit.